Zdravstvene storitve kot ekonomska dobrina - Brščič, Bernard (Zdravstveno varstvo, 2007)
The authors discuss the nature and significance of health and health services.The definition of health services has an important economic, political and ethical impact on health policy-making and, consequently plays an important role both in determining the extent of services to be left to market mechanisms, and the extent of government involvement in their delivery.If health services are to be awarded a special status and role in health provision, this opens an important ethical dimension of social justice,which transcends the neutrality of economic discourse. Modern moral philosophy offers multiple theories of justice (i.e. utilitarian, egalitarian,deontological and libertarian-entitlement), and therefore allows for the adoption of different models of health care systems. Because of different ethical foundations and conceptions of justice, these theories provide divergent results reducing the discussion on optimal health care system to a debate about the true significance of fundamental values of liberty, individual autonomy, equality and justice.
Keywords: javne dobrine; zdravje; zdravstvene storitve